2001
DOI: 10.1046/j.0742-3071.2001.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain natriuretic peptide increases urinary albumin and alpha‐1 microglobulin excretion in Type 1 diabetes mellitus

Abstract: Intravenous infusion of BNP and ANP both increase the urine excretion of albumin and the tubular protein alpha1 microglobulin, independent of creatinine clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Yano et al have shown that the plasma BNP level was significantly associated with the degree of microalbuminuria in normotensive diabetic patients without any cardiac dysfunction [12]. McKenna et al have reported that intravenous infusion of BNP increased the urine excretion of albumin in patients with Type 1 diabetes [13]. These reports appear to suggest that BNP might be related to the presence of diabetic complications.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Yano et al have shown that the plasma BNP level was significantly associated with the degree of microalbuminuria in normotensive diabetic patients without any cardiac dysfunction [12]. McKenna et al have reported that intravenous infusion of BNP increased the urine excretion of albumin in patients with Type 1 diabetes [13]. These reports appear to suggest that BNP might be related to the presence of diabetic complications.…”
mentioning
confidence: 86%
“…Thus, it is likely that BNP may be useful as a potential biomarker for the severity of CHF in diabetic patients. In addition, several investigators, but not all, have recently shown that the plasma BNP level could be elevated in association with the presence of diabetic complications [12,13]. Indeed, diabetes mellitus has the possibility to induce sodium retention and volume expansion, eventually affecting the cardiac hormone systems.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with heart failure, deceased clearance from the kidneys contributes to the elevated BNP level [17]. Among patients with type 1 diabetes mellitus, BNP infusion increased urine excretion of albumin [18]. Low clearance of BNP might therefore increase urine excretion of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…One clamp study has shown that BNP infusion increases urine albumin excretion in patients with type I diabetes. 26 It was reported that this may be due to a downregulation of A-type guanylate cyclasecoupled natriuretic peptide receptors in renal tubules or due to elevated NT proBNP levels leading to higher glomerular hydraulic pressure or higher capillary permeability and possibly increased albumin excretion. 27 Zietse et al and McKenna et al 26,28 have shown that during ANP infusion, albumin excretion increases in diabetic patients and suggested that ANP increases the transcapillary escape rate of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…26 It was reported that this may be due to a downregulation of A-type guanylate cyclasecoupled natriuretic peptide receptors in renal tubules or due to elevated NT proBNP levels leading to higher glomerular hydraulic pressure or higher capillary permeability and possibly increased albumin excretion. 27 Zietse et al and McKenna et al 26,28 have shown that during ANP infusion, albumin excretion increases in diabetic patients and suggested that ANP increases the transcapillary escape rate of albumin. Because both ANP and BNP bind to the same receptor and have the same biological activity, it is conceivable that abnormally elevated levels of BNP also cause increased glomerular hydraulic pressure and thus induce increased albumin excretion in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%